The Effect of Ginger on Lowering Blood Pressure in The Elderly - Widya Lusi Arisona; Pande Ayu Naya Kasih Permatananda; Cahyaning Rini Utami; Imam Jayanto; Ertati Suarni (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
Hypertension is a significant global health challenge, especially in the elderly population experiencing decreased vascular physiological function. This study aims to analyze the effectiveness of ginger (Zingiber officinale) intervention as a complementary therapy in lowering blood pressure in the elderly. Using a quantitative design with a quasi-experimental pre-test and post-test group approach, this study evaluated changes in systolic and diastolic blood pressure after regular administration of ginger extract. The results showed a statistically significant decrease in blood pressure ($p < 0,05$) in the intervention group compared to the control group. The hypotensive mechanism of ginger is associated with its role as a natural calcium channel blocker and angiotensin-converting enzyme (ACE) inhibitor. This study concludes that ginger can be used as a safe and effective nutraceutical alternative to help manage hypertension in the elderly, improving quality of life and reducing the risk of cardiovascular complications.